Treating Aging Changes of Facial Anatomical Layers with Hyaluronic Acid Fillers - Kapoor KM; Saputra DI; Porter CE; Colucci L; Stone C; Brenninkmeijer EEA; Sloane J; Sayed K; Winaya KK; Bertossi D (Dove Medical Press, 2021)
Krishan Mohan Kapoor,1,2 Deasy Indra Saputra,3 Catherine Ellen Porter,4 Ligia Colucci,5 Catherine Stone,6 Elian Elisabeth Anne Brenninkmeijer,7 Jake Sloane,8 Karim Sayed,9 Ketut Kwartantaya Winaya,10 Dario Bertossi11 1Anticlock Clinic, Chandigarh, India; 2Department of Plastic Surgery, Fortis Hospital, Mohali, India; 3Project Skin BMDerma Clinic, Jakarta, Indonesia; 4All Saints Skin Clinic, Darlinghurst, NSW, Australia; 5Clinica Ligia Colucci, Belo Horizonte, MG, Brazil; 6The Face Place Medspa, Auckland, New Zealand; 7Elian Brenninkmeijer Cosmetic Dermatology, Amsterdam, the Netherlands; 8Infinity Skin Clinic, Surry Hill, NSW, Australia; 9Faculty of Health and Social Sciences, University of South-East Norway, Drammen, Norway; 10Department of Dermatology, Udayana Public University Hospital, Bali, Indonesia; 11Department of Maxillo-Facial Surgery, University of Verona, Verona, ItalyCorrespondence: Krishan Mohan KapoorAnticlock Clinic, #1508, Sector 33 D, Chandigarh, 160022, IndiaTel +91-9814600600Email kmkapoor@gmail.comAbstract: The aging process affects every anatomical layer of the face. Improved knowledge of how aging occurs in each anatomical layer of the face has helped evolve the facial rejuvenation strategies with HA fillers. Understanding the age-related changes in the anatomical facial layers, including their time of onset and how the changes occur in the different tissue layers, an injector can provide much more targeted and refined HA filler treatments. As fillers' use has increased, there has been a distinct shift away from procedures lifting the skin and SMAS. We can selectively target the anatomical facial layers with HA fillers for more refined and predictable outcomes. An extensive range of HA filler variants is now available. Each filler type is optimized and designed to be injected into specific tissue planes for the best results. Knowing the predictable aging changes in the different tissue layers of the face is crucial as this guides the optimum filler choice. Working knowledge of the individual characteristics of the numerous HA-based products allows for their effective placement in the correct layer. Familiarity with the correct HA product may also help to minimize the downtime and risk of adverse events.Keywords: facial aging, facial anatomy, filler injections, filler procedures, fillers, hyaluronic acid, filler complications